Investigation of the interaction of the MILD regime with HiTAC and no-combustion regimes in combustion region diagrams - Srinivasarao, M.; Sorrentino, Giancarlo; Mahendra Reddy, V. (Frontiers in Energy Research, 2024)
Moderate or intense low-oxygen dilution combustion is vital for reducing emissions. Recent advancements have introduced regime diagrams for various reactant mixtures, highlighting no-combustion, Moderate or intense low-oxygen dilution, and high-temperature air combustion regions to analyze the overall operating range. However, studies on these diagrams are limited and often lack detailed analysis. This study focuses on the interaction of the Moderate or intense low-oxygen dilution regime with other regimes, particularly examining ignition delay time. Initially, ignition delay times are analyzed using regime diagrams for methane, propane, and syngas fuel mixtures. Calculations reveal a consistent ignition delay time range at the boundary between Moderate or intense low-oxygen dilution and no-combustion, varying with fuel type. To investigate further, combustion regime diagrams for methane and methane-hydrogen mixtures are developed, considering dilution levels and preheating effects with N2, CO2, H2O, and exhaust gas recirculation. These diagrams examine the spread of the Moderate or intense low-oxygen dilution regime and the ignition delay times at the boundaries. The upper and lower limits of the moderate or intense low-oxygen dilution regime are noted based on obtained ignition delay times. An emission-based analysis within these regimes is conducted to assess the effectiveness of techniques in achieving moderate or intense low-oxygen dilution combustion. Proposed ignition delay time range for the considered mixtures aims to maintain mixture within the moderate or intense low-oxygen dilution regime, ensuring lower emissions. This is also further proved with the numerical simulations. The study also explores the sensitivity of dilution level, mixture temperature, N2, CO2, H2O, and EGR on the Moderate or intense low-oxygen dilution regime.